Identification of a Sam68 Ribonucleoprotein Complex Regulated by Epidermal Growth Factor - Huot, Marc-Étienne (American Society for Biochemistry and Molecular Biology, 2009)
Sam68, Src associated in mitosis of 68 kDa, is a known RNA-binding protein and a signaling adaptor protein for tyrosine kinases. However, the proteins associated with Sam68 and the existence of a Sam68 complex, its mass, and regulation are, however, unknown. Herein we identify a large Sam68 complex with a mass >1 MDa in HeLa cells that is composed of ∼40 proteins using an immunoprecipitation followed by a mass spectrometry approach. Many of the proteins identified are RNA-binding proteins and are known components of a previously identified structure termed the spreading initiation center. The large Sam68 complex is a ribonucleoprotein complex, as treatment with RNases caused a shift in the molecular mass of the complex to 200–450 kDa. Moreover, treatment of HeLa cells with phorbol 12-myristate 13-acetate or epidermal growth factor induced the disassociation of Sam68 from the large complex and the appearance of Sam68 within the smaller complex. Actually, in certain cell lines such as breast cancer cell lines MCF-7 and BT-20, Sam68 exists in equilibrium between a large and a small complex. The appearance of the small Sam68 complex in cells correlates with the ability of Sam68 to promote the alternative splicing of CD44 and cell migration. Our findings show that Sam68 exists in equilibrium in transformed cells between two complexes and that extracellular signals, such as epidermal growth factor stimulation, promote alternative splicing by modulating the composition of the Sam68 complex.